Kebijakan Kriminal Anak dalam Kasus Narkotika: Perspektif Restorative Justice - Ade Irawan; Alwan Hadiyanto; Ciptono Ciptono (JURNAL USM LAW REVIEW, 2025)
This study aims to analyze criminal policy toward children involved in narcotics-related offenses and the urgency of applying a restorative justice approach within Indonesia’s juvenile criminal justice system. This issue is critical because children as offenders in narcotics cases are often subjected to repressive measures similar to those applied to adults, without adequate consideration of the principles of child protection and rehabilitation. This research employs a normative juridical method, incorporating both statutory and conceptual approaches. The sources of legal materials consist of primary, secondary, and tertiary legal materials, which are analyzed qualitatively and descriptively. The findings reveal that the imposition of repressive criminal sanctions on children in narcotics cases is inconsistent with the mandate of Law Number 11 of 2012 on the Juvenile Criminal Justice System, which prioritizes the best interests of the child. The novelty of this research lies in emphasizing that restorative justice is both feasible and relevant for narcotics cases involving children, through mechanisms such as diversion, penal mediation, and community-based rehabilitation. Therefore, it is necessary to strengthen legal policies that explicitly regulate the application of restorative justice in narcotics cases involving children, to achieve optimal legal protection and prevent recidivism.   Penelitian ini bertujuan untuk menganalisis kebijakan kriminal terhadap anak yang terlibat dalam tindak pidana narkotika serta urgensi penerapan pendekatan restorative justice dalam sistem peradilan pidana anak di Indonesia. Isu ini penting karena anak sebagai pelaku kasus narkotika sering kali diproses dengan pendekatan represif seperti orang dewasa, tanpa mempertimbangkan prinsip perlindungan anak dan rehabilitasi. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perundang-undangan dan konseptual. Sumber bahan hukum terdiri dari bahan hukum primer, sekunder, dan tersier yang dianalisis secara deskriptif kualitatif. Hasil penelitian menunjukkan bahwa penerapan sanksi pidana yang bersifat represif terhadap anak dalam kasus narkotika tidak sejalan dengan amanat Undang-Undang Nomor 11 Tahun 2012 tentang Sistem Peradilan Pidana Anak, yang menempatkan kepentingan terbaik bagi anak sebagai prioritas. Kebaruan penelitian ini terletak pada penegasan bahwa restorative justice layak dan relevan diterapkan pada perkara narkotika anak melalui mekanisme diversi, mediasi penal, dan pembinaan berbasis komunitas. Oleh karena itu, diperlukan penguatan kebijakan hukum yang secara tegas mengatur penerapan restorative justice pada perkara narkotika anak, agar tercapai perlindungan hukum yang optimal dan pencegahan residivisme.